The Effect of Wage and Work Discipline on The Performance of Honorary Employees at The Public Works and Spatial Planning Office (DPUPR) of Probolinggo Regency - Ghafur, Abd.; Airho, Siti Aulia Isfi (CV. Civiliza Publishing, 2025)
Discipline at work must be adhered to, where the existing work regulations are to improve employee performance, on the other hand, the Probolinggo Regency public works and spatial planning office will provide work wages according to the results of each employee's performance. The formulation of the problem in this research is (1) Does giving wages affect employee performance? (2) Does work discipline affect employee performance? (3) Do wages and work discipline affect employee performance? This research method uses quantitative research with a sample size of 31 respondents. The results of this research show that the results of the wage variable (X1) have a positive effect on employee performance, namely b = 0.002 or 2% and the work discipline variable (X2) has a positive effect on employee performance, namely b = 0.975 or 97.5%. So it can be concluded that the wage variable (X1) and the work discipline variable (X2) together (simultaneously) influence the employee performance variable (Y). This can be seen from the significance of the wage variable of 0.970, which means it is greater than the significance level used, namely 0.05. And it can also be seen from the tcount of 0.038, which means tcount is smaller than ttable, namely 0.286.